Professional profile of the graduate engineer of systems and computer by computers - Sarmiento Alvarado, Marisol Josefina (2019)
This research was carried out within the framework of the design of professional profiles by competencies in one of the areas of significant studies, such as Computer Science, whose objective was to build the professional profile of the graduate of the Professional Career of Systems and Computer Engineering of the Santo Domingo de Guzmán University. This research arises from the need to review the current design of the professional profile of the graduate in this study program and compare it with the professional labor demands of this new Peruvian society, through occupational analysis and based on the vision of the professional related to this career. The study was located within the post-positivist paradigm and its qualitative approach, from hermeneutics and using the grounded theory, the method used was the continuous comparative, as informants we worked with the students of the last cycle, specialized teachers and various companies related to Systems and Computer science, in order to know the current labor demand, as an instrument for the collection of information, the semi-structured interview was used, the protocol texts were created from which the sun category of research emerges and its subcategories, this allowed to design the matrix of occupational analysis that decays the professional profile of the graduate. Based on the results, a proposal is presented in accordance with the demands of this modern, trans-disciplinary world based on the integral formation of the student and whose educational process is centered on the student, in a society permeated by technology.